On Lower Bound for W(K2n) - Kamalian, Rafael R.; Petrosyan, Petros A. (Mathematical Problems of Computer Science, 2024)
The lower bound W(K2n) ≥ 3n – 2 is proved for the greatest possible number of colors in an interval edge coloring of the complete graph K2n.